Analisis Manajerial terhadap Persepsi Masyarakat Terhadap Manfaat Ekologis dan Ekonomis Ekosistem Lamun - Cahyani, Esti Rahma; Sihsubekti, Sasanti (Idarotuna : Journal of Administrative Science, 2024)
Seagrass ecosystems play a crucial role in supporting coastal ecology. Lamongan Regency, East Java, contains extensive seagrass beds along its coastline, with varying conditions from healthy to degraded. This study aims to analyze community perceptions of the ecological and economic benefits of seagrass ecosystems in the coastal areas of Lamongan. Conducted between November and December 2024, the research utilizes descriptive qualitative analysis. Findings indicate that the local community's perception of seagrass ecosystems is largely positive, with a good understanding of both the ecological functions and economic potential of seagrass beds. Furthermore, the community demonstrates a high level of awareness and active participation in conservation efforts. This study provides insights for developing community-based conservation strategies that integrate seagrass ecosystems into broader coastal management practices